High-mobility and low subthreshold swing amorphous InGaZnO thin-film transistors by in situ H2 plasma and neutral oxygen beam irradiation treatment. (23rd April 2023) - Wu, Chien-Hung; Mohanty, Srikant Kumar; Huang, Bo-Wen; Chang, Kow-ming; Wang, Shui-Jinn; Ma, Kung-jeng
Abstract: In this work, staggered bottom-gate structure amorphous In–Ga–Zn–O (a-IGZO) thin film transistors (TFTs) with high-k ZrO2 gate dielectric were fabricated using low-cost atmospheric pressure-plasma enhanced chemical vapor deposition (AP-PECVD) with in situ hydrogenation to modulate the carrier concentration and improve interface quality. Subsequently, a neutral oxygen beam irradiation (NOBI) technique is applied, demonstrating that a suitable NOBI treatment could successfully enhance electrical characteristics by reducing native defect states and minimize the trap density in the back channel. A reverse retrograde channel (RRGC) with ultra-high/low carrier concentration is also formed to prevent undesired off-state leakage current and achieve a very low subthreshold swing. The resulting a-IGZO TFTs exhibit excellent electrical characteristics, including a low subthreshold swing of 72 mV dec −1 and high field-effect mobility of 35 cm 2 V −1 s −1, due to conduction path passivation and stronger carrier confinement in the RRGC. The UV–vis spectroscopy shows optical transmittance above 90% in the visible range of the electromagnetic spectrum. The study confirms the H2 plasma with NOBI-treated a-IGZO/ZrO2 TFT is a promising candidate for transparent electronic device applications.